Load compensation techniques using multi-tapped potentiometers - Garner, K. C. (College of Aeronautics, 1960)
The theory is developed for loading error compensation techniques utilising multi-tapped potentiometers. Two methods of compensation are derived, and their relative advantages discussed. Design formulae are given for calculating appropriate values of the shunt resistors to be used in association with the tapped potentiometers. Numerical examples of each method are given.